IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT THROUGH THINK PAIR SHARE - Adly Syahputra; Elia Masa Ginting (Universitas Negeri Medan, 2012)
Students’ achievement in writing descriptive text is very low, in this study Think Pair Share (TPS) was applied to solve the problem. Action research in conducted for the result and the technique to collect the data, qualitative and quantitative are applied in this research. The subject of this research is grade VIII in Junior High School (SMP Bilang Huluh) Rantau Parapat. In the first evaluation (66,4375) increased to the mean of second evaluation (78,125) and the mean of third evaluation (87,5625). Observation result showed that the students gave their good attitudes and responses during teaching and learning process by applying the application of TPS (Think Pair Share) method. Questionnaire and interview report showed that students agree that the application of TPS (Think Pair Share) method had helped them in writing descriptive text. It can be conclude that the students’ achievement is improved when thay are tought through TPS Method. Key Words: Achievement, Writing, Descriptive Text and Think Pair Share